Internet of Things Training Set: A Modern Approach to Learning - Champa, Laddawan (Journal of Telematics and Informatics, 2025)
The purpose of this research were to design and construct of Internet of Things training set. The quality of this developed training set was evaluated by experts to find the efficiency. The samples of this research were students in industrial technology program, faculty of industrial technology who had been study of internet of things  system subject selected by  Stratified Sampling Technique. The research instrument were the internet of things training set, quality evaluation and worksheets. The result of the research revealed that the quality about the content aspect of the internet of things training set was at excellent level ( = 4.52), and the quality of worksheet was at excellent level ( = 4.58). The efficiency E1/E2 = 85.27/88.40 which statistical higher than criteria 80/80  at 0.05 significant level as hypothesis setting the efficiency not less than 80/80